Recommendations for people with osteoporosis and general practitioners during COVID-19 pandemic - Miškić, Blaženka (Array, 2020)
The paper presents the guidelines made by the Multidisciplinary Team for Osteoporosis for patients in the General Hospital “Dr.Josip Benčević”, Slavonski Brod and general practitioners in the Brod-Posavina County in order to inform them properly about the COVID-19 pandemic and the recommendations of the National Civil Protection Committee, as well as to help them reduce their fear and to improve their cooperation with their general practitioners. A system of recording new fractures in the county was maintained since the onset of the epidemic. The recommendations for patients with osteoporosis include their lifestyle, medical treatment and balanced nutrition, following the advices of the International Osteoporosis Foundation, the Croatian Osteoporosis Society and the British Royal Osteoporosis Society. Living with osteoporosis demands balanced nutrition, regular exercise and taking prescribed medications. As in the present conditions of COVID-19 epidemic outdoor physical activities are temporarily limited it is necessary to ensure the availability of calcium-rich food and vitamin D supplies. As medical treatment of osteoporosis does not increase risk of COVID-19 infection it is recommended for patients to continue their prescribed therapy in consultation with their general practitioner.